Production Performance of Catfish (Clarias gariepinus Burchell, 1822) Cultured With Added Probiotic Bacillus sp. on Biofloc Technology - Rifqah Pratiwi; Kurniawan Wahyu Hidayat; Sumitro Sumitro (Department of Aquaculture, 2020)
Biofloc technology (BFT) is one of the most developed aquaculture technologies, which aims to improve the efficiency of feed use by providing nutrients for flocs to be used by fish as a supplementary feed. Also, BFT serves to improve water quality through the breaking down of fish waste materials assisted by heterotrophic bacteria. Bacteria used in this study were Bacillus sp. as probiotics in BFT. This study aimed to examine the production performance of catfish maintained with a biofloc system on an industrial scale, without experimental design. The average weight of catfish when stocking was 5.9 ± 0.0 g/fish with a density of 7000 fish in 9 unit circular ponds. This studies showed after 78 days of culture, bodyweight gain about 28.6 g/fish to 41.7 g/fish, highest specific growth rate was K2 (2.4 ± 0.2% BW/day), the highest survival rate K2 (98.87 ± 6.64% BW/day), highest grow rate K1 (41.7 ± 5.8 g) and the best FCR K9 (0.95 ± 0.11).